Experimental Characterization of Damped CFRP Materials with an Application to a Lightweight Car Door. (24th August 2017) - Fasana, Alessandro; Ferraris, Alessandro; Airale, Andrea Giancarlo; Berti Polato, Davide; Carello, Massimiliana
Abstract : This paper presents a complete design procedure for defining a dynamic model of a Carbon Fibre Reinforced Polymer (CFRP) component with an embedded damping material layer. The experiment to determine the mechanical characteristics of the materials is performed by the Oberst beam technique to provide precise material properties for a Finite Element (FE) model. The technique implemented, namely, the Linear Identification by Polynomial Expansion in the Z-domain (LIPEZ) method, is used to compare the experimental data with the numerical simulation results provided by the modal parameters to be compared with the numerical results. Two automotive components (a leaf spring and an outer shell of front door) have been tested. The research revealed the utter importance of a correct definition of the geometry for the numerical models. Finally, the positive effects for acoustic performance with a thin layer of KRAIBON® SUT9609/24 damping material, included in the stacking sequence of the CFRP component, are highlighted.